Understanding Veteran Attitudes, Interests, and Needs around Virtual Care Applications. (December 2020) - Saleem, Jason J.; Moon, Brian; Bross, Emma; Anders, Shilo; Conway, Brandon; Wilck, Nancy R.; Frisbee, Kathleen L.; Herout, Jennifer
Given the substantial increase in interest and activity in the virtual care space, the Department of Veterans Affairs (VA) is making a concerted effort to increase opportunities for Veterans to adopt virtual care applications. We investigated Veteran attitudes, interests, and needs for virtual care applications, including privacy considerations and specific types of data they would be comfortable sharing with their providers through various Veteran-facing tools. We administered a 28-item questionnaire to 40 Veterans and performed follow-up interviews with a subset of nine Veterans. Study results revealed broad support by Veterans for using virtual care applications, including wearable devices, for sharing all types of health information with their providers. Further, Veterans expressed a desire for consolidation across VA-provided virtual care tools. Our findings will inform a strategy for Veteran-facing tools. Other health care systems may be interested in exploring these topics, based on our study results.